Tuberculosis incidence in foreign-born people residing in European countries in 2020 - Vasiliu, Anca; Köhler, Niklas; Altpeter, Ekkehardt; Ægisdóttir, Tinna Rán; Amerali, Marina; de Oñate, Wouter Arrazola; Bakos, Ágnes; D'Amato, Stefania; Cirillo, Daniela Maria; van Crevel, Reinout; Davidaviciene, Edita; Demuth, Irène; et al. (Euro surveillance, 2023)
BackgroundEuropean-specific policies for tuberculosis (TB) elimination require identification of key populations that benefit from TB screening.AimWe aimed to identify groups of foreign-born individuals residing in European countries that benefit most from targeted TB prevention screening.MethodsThe Tuberculosis Network European Trials group collected, by cross-sectional survey, numbers of foreign-born TB patients residing in European Union (EU) countries, Iceland, Norway, Switzerland and the United Kingdom (UK) in 2020 from the 10 highest ranked countries of origin in terms of TB cases in each country of residence. Tuberculosis incidence rates (IRs) in countries of residence were compared with countries of origin.ResultsData on 9,116 foreign-born TB patients in 30 countries of residence were collected. Main countries of origin were Eritrea, India, Pakistan, Morocco, Romania and Somalia. Tuberculosis IRs were highest in patients of Eritrean and Somali origin in Greece and Malta (both > 1,000/100,000) and lowest among Ukrainian patients in Poland (3.6/100,000). They were mainly lower in countries of residence than countries of origin. However, IRs among Eritreans and Somalis in Greece and Malta were five times higher than in Eritrea and Somalia. Similarly, IRs among Eritreans in Germany, the Netherlands and the UK were four times higher than in Eritrea.ConclusionsCountry of origin TB IR is an insufficient indicator when targeting foreign-born populations for active case finding or TB prevention policies in the countries covered here. Elimination strategies should be informed by regularly collected country-specific data to address rapidly changing epidemiology and associated risks.
Keywords: Evropa; Tuberculosis; refugees; Somalia; Cross-Sectional Studies; Somálsko; tuberkulóza; TB; incidence; Humans; průřezové studie; migrants; prevention; policy; Incidence; lidé; Europe